Effect of blood flow restriction technique on delayed onset muscle soreness: a systematic review - Rodrigues, S.; Forte, P.; Dewaele, E.; Branquinho, L.; Teixeira, J. E.; Ferraz, R.; Barbosa, T. M.; Monteiro, A. M. (Medicina, 2022)
Background and Objectives: The effect of the blood flow restriction technique (BFR) on delayed onset muscular soreness (DOMS) symptoms remains unclear. Since there is no consensus in the literature, the aim of the present study is to systematically identify and appraise the available evidence on the effects of the BFR technique on DOMS, in healthy subjects.